SHEIKH DJAMIL DJAHO AND SOCIO-RELIGIOUS CRITICISM OF MINANGKABAU MUSLIM: A Study on Tazkirat al-Qulub Fi Mu‘amalat ‘Allam al-Guyub - Bahri, Saeful (Analisa: Journal of Social Science and Religion, 2018)
This article discusses the socio-religious critique of Sheikh Djamil Djaho on the religious and socio-society conditions in Minangkabau. Analysis of the content and approach of social history-intellectuals was used to dissect the contents of the book Tazkirat al-Qulub associated with social-religious context in the policy at the beginning of the 20th century. Based on the analysis of texts it is known that Sheikh Djaho expressed his criticism towards several groups. Among the groups are (1) scholars, (2) worshippers, (3) Sufism experts, and (4) experts of the world. According to Sheikh Djaho, the four groups might include gurur (faction), when they use intelligence in their respective fields as masks, not in honesty. This study shows three points. First, the presence of Sheikh Djaho's criticism departs from the reality of the life of the clergy and layman at that time. Second, the reality of social life keeps a text alive in society. Third, the solution to social-religious reality in the early 20th century was the practice of tasawwuf.